Performance Differential between India’s State Owned Ratna Companies and Private Owned Enterprises - Nagale, Abhay S. (International Journal of Economics and Financial Issues, 2017)
It is generally believed that state owned enterprises are less profitable and efficient compared to private owned enterprises (POE). The objective of this study is to examine whether there is any difference in the profitability and efficiency of India’s state owned Ratna companies and POE. The period in this study spans from 2007 to 2016 and the sample consists of 71 Ratna companies and 332 POE. Return on shareholders fund, return on total assets and productivity of capital are used as measure of performance. The findings show that Ratna companies perform worse that POE. Keywords: Performance, Private owned companies, Government linked companies JEL Classification: G